The Hydrogen Potential Assessment based on Wind and Solar Energy in Elazig Province, Türkiye - Calıskan, Abuzer; Percin, Hasan Bektas (My University, 2025)
This study investigates the feasibility of hydrogen production potential using the available renewable energy source potentials in the province of Elazig, Türkiye. The study aims to create a potential assessment of each district in Elazig, based on wind and solar sources and Proton Exchange Membrane (PEM) electrolyzer technology. It aims not only to evaluate the green hydrogen potential but also to outline the feasibility of implementing this alternative energy source at a localized level. In this way, an alternative energy source can be assessed for production, storage, and the scarcity of energy in emergency conditions such as earthquakes or other cases. The comprehensive analysis integrates a multitude of parameters, including geographic variations and technological considerations, supported by detailed illustrations to present a holistic view of the hydrogen potential in Elazig. The study’s outcomes suggest that districts with high energy potential and minimal geographical and topological constraints have a significant potential for hydrogen production.
Keywords: Wind Energy; Solar Energy; Green Hydrogen; PEM Electrolyzer